STRATEGI DIGITAL MARKETING DALAM MENINGKATKAN DAYA SAING UMKM KULINER DI KOTA SAMARINDA KALIMANTAN TIMUR - Dessi Nur Hidayah (Jurnal Ekonomi dan Bisnis, 2026)
The development of digital technology has brought about significant changes in the business world, including within the culinary Micro, Small and Medium Enterprises (MSMEs) sector. Digital marketing has become an effective marketing strategy in helping MSMEs enhance their business competitiveness and reach a wider consumer base. This study aims to analyse digital marketing strategies among culinary MSMEs in the city of Samarinda. The research employs a qualitative descriptive approach, utilising data collection techniques such as observation, documentation, and literature review. The findings indicate that culinary MSMEs in Samarinda utilise social media platforms such as Instagram, TikTok, and WhatsApp Business as digital promotional tools. Marketing strategies are implemented through content marketing, online promotions, the use of attractive product visuals, and active interaction with consumers. The use of digital marketing is considered capable of increasing brand awareness, expanding marketing reach, and boosting consumer interest in culinary products. Thus, digital marketing strategies play a vital role in supporting the development of culinary SMEs in Samarinda